Categorization of retail according the added values percieved by the consumers of the socialeconomic degrees 3 and 4 of Bogotá, Colombia (GEON Journal (Management, Organizations and Business), 2019)
This article is the result of a research, whose main objective was to identify the category of retail distribution channels, according to the added values perceived by consumers of socioeconomic levels 3 and 4 of Suba District in Bogota. It was carried an exploratory qualitative investigation out, with the application of non-probabilistic snowball sampling and data collection instruments through semi-structured interviews and focus groups, which allowed the identification of ​​perceived values by consumers in front of products and services offered by the establishments.  The results indicated that values ​​such as quality, location, promotion, offer and service, represent greater importance than the knowledge of the kind of retail establishment visited, so that consumers do not identify a classification of intermediaries and, on the contrary, they consider the mentioned values.
Keywords: Distribution Channels; perceived values; categorization of establishments; consumption